A Rare Case of Lipidized Fibrous Histiocytoma of the Oral Cavity - Shimada, Katsumitsu; Murakami, Satoshi; Hasegawa, Hiromasa (Curēus (Palo Alto, CA), 2025)
Benign fibrous histiocytoma (FH) is a common cutaneous tumor that rarely occurs in the oral cavity. Lipidized FH is an uncommon variant characterized by abundant foam cells in collagenized stroma. To our knowledge, only a single case of oral lipidized FH affecting the tongue has been reported. We examine a case of lipidized FH in the buccal mucosa of a patient presenting with a gradually enlarging, pedunculated lesion measuring up to 26 mm. A histological examination revealed a well-marginated but unencapsulated tumor with a Grenz zone, hyalinized stroma, and central foam cell aggregation. Immunohistochemically, the spindle and foam cells were CD68-positive, with focal Factor XIIIa positivity and negative bcl-2 staining. The lesion was completely excised, and no recurrence was observed. To our knowledge, this is the second reported case of oral lipidized FH and the first case in the buccal mucosa. Given its rarity and histological overlap with other xanthomatous lesions, accurate diagnosis is crucial with immunohistochemistry. Complete excision appears to be curative; however, a long-term follow-up is recommended, considering the subtype of fibrous histiocytoma developing in the orofacial region.